Effects of Climate Variability on Malaria Prevalence in Bauchi Local Government Area, Bauchi State, Nigeria - Abdulsalam, Mohammed; Abdullahi, Ahmed C.; Abdulkareem, Jamil Hassan; Sadiq, Malam Lukman S. (Kwaghe International Journal of Sciences and Technology, 2025)
This study examined the impact of climate variability on malaria prevalence in Bauchi Local Government Area, Nigeria, using a retrospective survey design. Archival data on climate variables, temperature (maximum and minimum), rainfall, and relative humidity, were obtained from the National Aeronautics and Space Administration (NASA), while epidemiological records of malaria cases were sourced from the Bauchi State Agency for the Control of HIV/AIDS, Tuberculosis, and Malaria (BACATMA), as well as from international databases including WHO, IPCC, and WMO. Data covering the period from 2008 to 2018 were analyzed using descriptive statistics, trend analysis, and Pearson’s correlation, implemented through SPSS version 26 and XLSTAT 2017. Trend analyses revealed notable climate variability, with annual rainfall peaking at 1301.83 mm in 2012 and reaching a low of 761.95 mm in 2016. Maximum temperatures ranged from 24.5°C in 2008 to 30.1°C in 2018, while relative humidity fluctuated between 52.5% in 2008 and 37.3% in 2018. Malaria cases exhibited a sharp increase from 2015, peaking in 2016 (291,607 cases), with consistently high figures in 2017 and 2018. Correlation analysis found no statistically significant relationship between malaria prevalence and rainfall (r = –0.050, p = 0.566), minimum temperature (r = 0.114, p = 0.194), or relative humidity (r = –0.080, p = 0.361). However, a strong positive and statistically significant correlation was observed between malaria prevalence and maximum temperature (r = 0.974, p = 0.030). These findings suggest that maximum temperature is a key climatic driver of malaria transmission in the region, highlighting the need for climate-informed disease surveillance and control strategies.